2018
DOI: 10.1162/jocn_a_01314
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Object Weight Processing after Bilateral Lateral Occipital Complex Lesions

Abstract: Object interaction requires knowledge of the weight of an object, as well as its shape. The lateral occipital complex (LOC), an area within the ventral visual pathway, is well known to be critically involved in processing visual shape information. Recently, however, LOC has also been implicated in coding object weight before grasping-a result that is surprising because weight is a nonvisual object property that is more relevant for motor interaction than visual perception. Here, we examined the causal role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Dijkerman et al (2004) found that patient SB, who has visual agnosia as a consequence of damage sustained at 3 years old, experiences no visual size-weight illusion but does experience a kinaesthetic size-weight illusion. In contrast, Buckingham, Holler, Michelakakis, & Snow (2018) found that patient MC -who also sustained damage to the visual ventral stream -experiences a visual size-weight illusion that is statistically indistinguishable from that of controls. Patient MC's size-weight illusion was, however, smaller than that of 10/12 of Buckingham, Holler, Michelakakis, & Snow's (2018) controls.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Dijkerman et al (2004) found that patient SB, who has visual agnosia as a consequence of damage sustained at 3 years old, experiences no visual size-weight illusion but does experience a kinaesthetic size-weight illusion. In contrast, Buckingham, Holler, Michelakakis, & Snow (2018) found that patient MC -who also sustained damage to the visual ventral stream -experiences a visual size-weight illusion that is statistically indistinguishable from that of controls. Patient MC's size-weight illusion was, however, smaller than that of 10/12 of Buckingham, Holler, Michelakakis, & Snow's (2018) controls.…”
Section: Introductionmentioning
confidence: 74%
“…In contrast, Buckingham, Holler, Michelakakis, & Snow (2018) found that patient MC -who also sustained damage to the visual ventral stream -experiences a visual size-weight illusion that is statistically indistinguishable from that of controls. Patient MC's size-weight illusion was, however, smaller than that of 10/12 of Buckingham, Holler, Michelakakis, & Snow's (2018) controls. This reduced size-weight illusion magnitude may represent a modest deficit in MC, which Buckingham, Holler, Michelakakis, & Snow (2018) may have been unable to detect due to low statistical power (Figure 2a).…”
Section: Introductionmentioning
confidence: 74%
“…Previous clinical evidence suggested a possible role for the posterior parietal cortex, but results were mixed (Li et al, 2007, 2011). It seems likely instead that other areas are more involved in the SWI, such as the ventral premotor cortex (Chouinard et al, 2009) or the lateral occipital cortex (Gallivan et al, 2014), although lesions this latter area did not seem to affect the SWI (Buckingham et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This was an interesting result, since this area is also known to be involved in visual as well as haptic object perception (Amedi, Jacobson, Hendler, Malach, & Zohary, 2002; Amedi, Malach, Hendler, Peled, & Zohary, 2001) and especially involved in the representation of object shape (Kourtzi & Kanwisher, 2001). However, it was recently shown that bilateral lesions to the lateral occipital cortex did not affect perception of the SWI in a stroke patient (Buckingham, Holler, Michelakakis, & Snow, 2018), leaving it unclear whether this region has a causal role in weight perception.…”
Section: Introductionmentioning
confidence: 99%
“…Significant associations with PP scores were also found for Occipital Mid L and Temporal Mid L doses. Indeed the first area has an important role in coding object weight prior to grasping [43] and in object-directed action [44]. The second area is involved in many functions among which, motion [45] and grasp observation [46] and probably also in self-grasp observation, by a mechanism of mirroring.…”
Section: Plos Onementioning
confidence: 99%